A missiology of progress: Assessing advancement in the Bible translation movement - Franklin, Kirk (HTS teologiese studies, 2020)
Statistical analysis has been a common method for determining progress in missional activity. In the case of Bible translation, measurable statistics have been readily available showing progress. However, there have been gaps such as biblical, sociological, theological and missiological factors. The aim of this study is to consider broader factors than just quantifiable measurements that could be used to develop a missiological foundation for missional progress, especially for Bible translation. The setting was to analyse inputs from leaders within the Bible translation movement in terms of their understanding of the factors to be considered for a missiology of progress. Using a qualitative study based upon a questionnaire, the researcher grouped the responses by common categories and then analysed the key findings. The qualitative nature of how Bible translation was conducted reveals important factors such as signs of increased collaboration between Bible translation agencies, improved quality of relationships between Bible translation agencies and the local church, and also theologically significant milestones. The study concludes that progress in the Bible translation movement has to be considered within the broader context of God’s mission. Church history has revealed how progress in one era could be regress in another era. Consequently, reflecting and learning together within the Bible translation movement has been a key to progress, and therefore, all participants in the Bible translation movement have been called to work and learn together.